(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. L’Islam tra le mura del carcere: le ragioni di un intervento, gli obiettivi del Protocollo - 2. Uno spiraglio di libertà: la fede in regime di detenzione, le garanzie normative e le risposte alla diversità religiosa - 3. Mediatori o ministri di culto? Un ruolo ‘sospeso’ tra definizioni giuridiche e prassi - 4. Visitate i detenuti: La questione dell’ingresso negli istituti detentivi, criticità applicative e novità del Protocollo - 5. Conclusioni. Granting Islamic religious ministers admission to prisons, amid long-lasting issues and reformation perspectives. The Agreement between the Prison Administration Department and the Islamic Communities Union. ABSTRACT: As religious diversity in Italian prisons grows, accommodating prisoners’ religious needs tries legal paradigms and instruments out. In 2015 the Prison Administration Department signed an agreement with UCOII, one of the largest Islamic associations in Italy, in order to grant admission in prisons to intercultural mediators and religious ministers. This article seeks to situate the covenant in the wider context of the Italian legal protection of religious freedom in prison, highlighting three main purposes of the agreement: providing Islamic prisoners with religious assistance, enforcing rehabilitative programs and combating violent radicalization in jail. After two years the experience has shown good evidences. Nonetheless, contended issues still remain unsettled. While evaluating feasible solutions, the article advocates a legislative intervention that could assess criteria and procedures for religious ministers’ access to prisons fulfilling the principle of equality and non-discrimination.